Disciplinary Struggles in Education - Heikkinen, Anja (Tampere University Press, 2019)
This book discusses disciplinary struggles in education from three perspectives. The chapters in the first section analyse the disciplinary character of educational practice and institutions. The second section focuses on justification of educational knowledge in transmission between theory and practice. The contributions of the third section problematise the aims and functions of educational practice and theory, which are critical for understanding the implications of disciplinary struggles in education for the future. Although the chapters focus on certain historical periods, forms and contexts of education, they provide insights, which are useful and relevant for a wider discussion in the eclectic and diverse theories and practices of education.